The Role of Enjoining Good and Forbidding Evil in Shaping Social Life According to the Arba'in Nawawi - Basyir, Damanhuri (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
Al-Arba’in al-Nawawiyah is recognized as one of the most celebrated collections of hadith in the Islamic scholarly tradition. Compiled by Imam al-Nawawi, this work brings together forty-two carefully selected authentic sayings of the Prophet Muhammad (peace be upon him), encompassing the essential pillars of Islamic teachings including theology (aqidah), worship (ibadah), jurisprudence (fiqh), ethics (akhlaq), and social interactions (mu'amalah). Due to its concise yet comprehensive content, this compilation has served as a foundational reference in Islamic education across the Muslim world. Among the core themes explored in this collection is the concept of amar ma’ruf nahi munkar the imperative to promote good and prevent wrongdoing. This principle is not limited to personal piety but plays a vital role in shaping a morally conscious and socially cohesive community. The aim of this study is to examine how this concept is presented in Al-Arba’in al-Nawawiyah and interpreted across generations through numerous sharh (commentaries) by classical and contemporary scholars. Adopting a qualitative-descriptive approach through textual analysis, this study investigates more than fifty-one commentarial works on Al-Arba’in al-Nawawiyah. The analysis focuses on hadiths directly related to amar ma’ruf nahi munkar, with particular attention to how scholars employ both linguistic (lughawi) and legal (fiqhi) frameworks using analytical (tahlili) and general (ijmali) methods to extract meaning and explore social implications. Findings reveal that linguistic and legal interpretations in these commentaries enrich the understanding of the relevant hadiths and underscore the broader societal function of amar ma’ruf nahi munkar. Rather than a mere moral exhortation, the principle emerges as a strategic tool for fostering collective responsibility, preserving ethical order, and nurturing a just and compassionate society. It thus stands not only as a religious obligation but as a cornerstone of Islamic social ethics.